Energy harvesting based on piezoelectric ericsson cycles in a piezoceramic material - Bin Zhang; Duchame, Benjamin; Sebald, Gael; Guyomar, Daniel (Proceedings - IEEE International Symposium on Applications of Ferroelectrics, 2014)
Energy harvesting has been studied with great interest in recent years. Ambient vibration is a potential energy resource for low-power devices or electronic devices in extreme/remote area. Methods on enhance the energy conversion amount has been long been a main subject in energy harvesting field. The present study developed a precise model working under hybrid of electrical and mechanical excitations in an Ericsson loop cycles which highly increases the converted energy. Consideration of the dynamic behavior of the nonlinearity of the piezoceramic under high amplitude excitation, the model gives precise prediction of energy conversion amount. This technique can be applied in both energy harvesting and monitoring area. Experiments have been done for different kinds of samples. Comparisons between energy conversion with or without the new coupling technique have been reported and it allows validating this new configuration.